PERSPECTIVE STUDY OF THE AgNPs EFFECT ON THE MATERNAL AND EMBRYONIC DEVELOPMENT IN ALBINO RATS - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to displayed effect of this nanoparticles on pregnant mother and embryos. All females administration of AgNPs suspension orally during the gestational period (for 21day) in two doses low 2mg and high dose 20 mg /Kg body weight and the control group received D.W only. The pregnant females (60 females) include the control group and the treated group  was subdivided in to two groups, pre and post implantation and all the mothers weighted along the study. The embryos and their brains after retrieved weighted and the crow-rump length (CRL) measurement also. The results showed that the active form of Ag can be transport the placental barrier and blood brain barrier (BBB). This nanoparticles showed adverse effect and produced decreased in mothers weights in low dose 2mg/Kg/ B.Wt and higher dose 20mg/Kg/ B.Wt. Weights of embryos were lower clearly after exposure to AgNPs compare to control group. On the other hand, the weights of embryo's brain were decreased compare of control group in both doses. The CRL of embryos lowered after exposure to AgNPs in treatment groups when compare to control group.